السرد التاريخي في رواية نهاية الصحراء لسعيد خطيبي - جباري, عائشة; دركي, آمنة; قسومة, أمال; شاوي, صفية (University of Eloued جامعة الوادي, 2024)
في رواية "نهاية الصحراء" للكاتب الجزائري سعيد خطيبي، نلاحظ أن الغلاف يحمل العديد من الدلالات المخبوءة والرسومات التي تعكس محتوى الرواية بطريقة مثيرة لفضول القارئ. كما تتعدد الشخصيات ما بين تاريخية وخيالية، ويبرع الكاتب في تداخل الزمن التاريخي والخيالي عبر تقنيات سردية كالاسترجاع. للمكان أيضًا دور بارز في سرد الأحداث، مع تنوعه بين الواقعي والمتخيل، ويتناوب الرواة في سرد القصة، مما يعطيها مصداقية وواقعية. ويستحضر الراوي فترة تاريخية لمعالجة الواقع الراهن، فتلغى المسافة بين الرواية والتاريخ، وتتعدى الرواية مجرد عرض جريمة القتل إلى تمثيل طبقات المجتمع الجزائري وأهم التحولات السياسية والاجتماعية التي تجسدت في شخوصها. In the novel "The End of the Desert" by the Algerian writer Saeed Khatibi, we note that the cover carries many hidden connotations and illustrations that reflect the content of the novel in a way that arouses the reader's curiosity. The characters are also diverse, both historical and fictional, and the writer excels in the interweaving of historical and fictional time through narrative techniques such as flashback. The place also plays a prominent role in the narration of events, with its diversity between the real and the imagined. The narrators alternate in telling the story, which gives it credibility and realism. The narrator evokes a historical period to address the present reality, thus eliminating the distance between the novel and history. The novel goes beyond a mere presentation of the crime of murder to a representation of the layers of Algerian society and the most important political and social transformations embodied in its characters.
أدب حديث ومعاصر